Integrated analysis of gene networks and cellular functions identifies novel heart failure biomarkers - Jiang Juncheng; Chen Lei; Lin Hao; Liang Fei (Hereditas)
Abstract Introduction Heart failure (HF) is a complex clinical condition characterized by impaired cardiac function and progressive structural remodeling. To elucidate the molecular mechanisms driving HF, this study aimed to identify key regulatory hub genes, explore their functional relevance, and assess their diagnostic and therapeutic potential. Methods Four public microarray datasets (GSE161472, GSE147236, GSE116250, and GSE46224) were retrieved from the Gene Expression Omnibus (GEO) database. Differential expression analysis using the limma package in R identified Differentially expressed genes (DEGs), which were further analyzed via Venn diagrams, STRING PPI networks, and Cytoscape’s CytoHubba plugin to determine top hub genes. RT-qPCR and Western blotting were used to validate gene expression in HF and normal cardiomyocyte cell lines. Functional assays (proliferation, colony formation, and wound healing) were conducted following overexpression of COL9A1 and MTIF3. miRNA regulation and immune cell infiltration were analyzed using TargetScan and CIBERSORT, respectively. Enrichment analysis was performed via DAVID, and drug prediction was conducted using DGIdb. Results Four hub genes—COL9A1, MTIF3, MRPS25, and HMGN1—were consistently downregulated in HF and exhibited high diagnostic potential (AUC > 0.8). Overexpression of COL9A1 and MTIF3 significantly reduced cell proliferation, colony formation, and migration in HF cell lines. Immune infiltration analysis revealed strong negative correlations between hub gene expression and various immune cell types. Drug prediction identified Milrinone as a potential therapeutic candidate targeting COL9A1. Conclusion COL9A1, MTIF3, MRPS25, and HMGN1 emerge as critical biomarkers and regulators in HF, offering promising avenues for diagnosis, mechanistic understanding, and targeted therapy development.